Pós-graduação stricto sensu como lugar/espaço da formação de professores da educação básica - Bitencourt, Juverci Fonseca (2022)
This study investigates the demarcations of educational policies in the National Postgraduate Plans (V and VI PNPG, 2005-2020), documents and evaluations in the areas of Education and Teaching (three-year and four-yearly, 2009-2019) and in academic production, which authorize treating stricto sensu training as a place/space for continuing education for basic education teachers. It uses a qualitative approach, split between documentary and bibliography (RICHARDSON, 2012) and review studies (VOSGERAU, ROMANOWISKI, 2014). It analyzes 22 theses and dissertations, available virtually, at Banco Digital Brasileiro de Teses e Dissertações (BDTD) and at Plataforma Sucupira, defended between the years 2005 and 2021, which support postgraduate training. It aims to understand the epistemologies that permeate the texts and examine the meanings produced about training in academic debates. It argues that there is an alignment between the rationality of postgraduate policy and academic production, theses and dissertations, however, taken as a space for training, it creates, due to the deviations of its nature and consensus, the opportunity for the development of professionalism (NÓVOA, 1991, 2002, 2017; CONTRERAS, 2012). It presupposes the master's and doctorate as a public good and a right for teachers. As epistemological support, concepts such as space and place, operation and theory, practice, institutionality, writing texts, textual interpretation, tactics, strategies, deviations and occasion were mobilized from Certeau (1994, 2012, 2015). The results indicate that there are tensions in the field of academic debate and between epistemological conceptions about teacher training at a stricto sensu level. He pointed out as a real implication that the analyzed researches maintain an approximation with postgraduate policies as an act of producing effects of truths that ratify his argument in favor of postgraduate studies to train teachers, based on meritocratic rationality, on the logic of the market and on a practical training. However, as an occasion, it was identified that the training of teachers at the postgraduate level, presents significant results such as valorization and professional development, articulation between theory and practice, qualification of professional practice and teaching, making this place a space for training at the deviate from some of politics and rationalities, producing a tactical formative movement observed in micro studies. He noted the urgency in the attention to be given to the theoretical-methodological aspects of academic production, requiring greater methodological rigor and fruitful reflection on the uses of academic consensus in the field of continuing teacher education in stricto sensu graduate programs.